2012
DOI: 10.2139/ssrn.1965921
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Firm-Initiated Clawback Provisions on Earnings Quality and Auditor Behavior

Abstract: While firm-initiated compensation recovery (or clawback) provisions are gaining popularity and the recently enacted Dodd-Frank Act seeks to make the clawback of erroneously awarded compensation mandatory for all listed companies, little is known about their effectiveness. We find that the incidence of accounting restatements declines after firms initiate such provisions. In addition, we show that investors and auditors view such provisions as associated with increased accounting quality and lower audit risk. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
143
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 62 publications
(156 citation statements)
references
References 43 publications
13
143
0
Order By: Relevance
“…Duchin et al 2010;Chan et al 2012). Note, however, that for clean inferences treatment should be assigned randomly over firms, which is not the case in our setting.…”
Section: Difference-in-difference Methodsmentioning
confidence: 91%
“…Duchin et al 2010;Chan et al 2012). Note, however, that for clean inferences treatment should be assigned randomly over firms, which is not the case in our setting.…”
Section: Difference-in-difference Methodsmentioning
confidence: 91%
“…Chan et al (2012) examined companies that have initiated compensation recovery provisions ('clawbacks') under Section 304 of the Sarbanes-Oxley Act of 2002 (SOX). They suggested that companies who initiate clawbacks are perceived to have higher accounting quality and lower audit risk, as indicated by shorter ARL for these companies.…”
Section: Performance and Financial Conditionmentioning
confidence: 99%
“…
a b s t r a c t Chan et al (2012) find that voluntary adoption of compensation clawback provisions is followed by fewer financial restatements and fewer auditor reports of material internal control weaknesses, higher earnings response coefficients, and reduced auditing fees and lags. They conclude that voluntary adoption of clawback provisions leads to increased financial integrity.
…”
mentioning
confidence: 99%